Diasporic Imagination and Chronotopes: Language Ideologies in Two Hungarian Diasporic Groups in Catalonia - Szabó, Gergely (Acta Universitatis Sapientiae, Philologica, 2023)
The ways diasporic groups emerge and diasporic identities are constructed have recently become important research topics in sociolinguistics. However, these works have not paid sufficient attention to the spatial-temporal configurations of diasporic imaginations. In this article, I intend to shed light on the ways differing diasporic imaginations are inscribed on what kind of language-related diasporic activities are created by the diasporic subjects. To answer this question, I draw on the data of an ethnographically informed critical sociolinguistic study of diasporization among Hungarians in Catalonia that I conducted between 2018 and 2022. In the analysis, I compare the chronotopic figures appearing in the life journey narratives of Hungarians in Catalonia with the ways the ideal diasporic subject was imagined in the activities of two salient diasporic organizations. The article points to the fact that diasporic imaginations do not only contain moral guidelines on how diasporic subjects should behave, but they are also determined by the time and the space diasporic subjects inhabit.